2014
DOI: 10.1128/jvi.01815-13
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Codetermines Tissue Tropism of Hepatitis C Virus and Is Crucial for Viral Cell-to-Cell Transmission by Contributing to a Postenvelopment Step of Assembly

Abstract: cHepatitis C virus (HCV) predominantly infects human hepatocytes, although extrahepatic virus reservoirs are being discussed. Infection of cells is initiated via cell-free and direct cell-to-cell transmission routes. Cell type-specific determinants of HCV entry and RNA replication have been reported. Moreover, several host factors required for synthesis and secretion of lipoproteins from liver cells, in part expressed in tissue-specific fashion, have been implicated in HCV assembly. However, the minimal cell t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
115
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(128 citation statements)
references
References 74 publications
9
115
3
1
Order By: Relevance
“…The horizontal bars represent the median values. HCVfrg, n ϭ 9; HCVcc, n ϭ 3. apoE function, our findings suggested that apoE is an essential factor for entry of infectious in vivo produced virus (23,(42)(43)(44)(45)(46).…”
Section: Hcvfrg Infectious Particles Have a Lower Density As Comparedmentioning
confidence: 91%
“…The horizontal bars represent the median values. HCVfrg, n ϭ 9; HCVcc, n ϭ 3. apoE function, our findings suggested that apoE is an essential factor for entry of infectious in vivo produced virus (23,(42)(43)(44)(45)(46).…”
Section: Hcvfrg Infectious Particles Have a Lower Density As Comparedmentioning
confidence: 91%
“…This is consistent with the report from Barretto et al 33 Engineering nonhepatic cells to produce HCV through ectopic apoE expression can confer cell-to-cell transmission capacity, albeit to a limited degree relative to the levels observed in the current study. 34 We thus cannot exclude that epitopes not recognized by the utilized anti-apoE antibody play a role in cell-to-cell transmission or that this antibody may have limited access to the virus during this process.…”
Section: Discussionmentioning
confidence: 99%
“…CD81 29 , RACK1 30 , PI4KIIIα [31][32][33] , and ApoE 8,12,17,34 are important cellular factors in HCV entry, IRES-mediated translation, RNA replication, and assembly, respectively. To determine the specific stage of the HCV life cycle that requires CIDEB, a panel of siRNAs targeting these genes was used.…”
Section: Resultsmentioning
confidence: 99%